Implications of the Concept of Absolute and Relative Truth on the Development of Islamic Education - Syauqi Musfirah Daud Pisba; Fatimah Azzahra; Putri Nadina Shafira Islamy; Choirul Astrian Saputra; Siti Uswatun Hasanah; Sayid Qutub (Al-Ulum: Jurnal Pendidikan Islam, 2026)
Differences in religious understanding in Islam often have an impact on educational practices that are less balanced between normative and contextual aspects. This shows the importance of understanding the relationship between absolute truth and relative truth in the development of Islamic education. This research aims to analyze the concept of absolute and relative truth and its implications for Islamic education. The method used is qualitative research with a library research approach, using primary sources of the Qur'an and hadith as well as scientific literature as secondary sources. The results of the study show that absolute truth functions as the foundation of fixed educational values and goals, while relative truth plays a role in the development of contextual educational methods and implementation. This finding confirms the importance of a balance between the two in building Islamic education that is relevant to the times. Therefore, the development of Islamic education needs to integrate normative values with adaptive approaches in order to produce learning that is critical, inclusive, and responsive to the needs of society.